Strategies for the quantification and characterization of nanoplastics in AOPs research - Di Luca, Carla (2024)
There is a growing interest in developing new targeted degradation technologies for the removal of micro- and nanoplastics (NPs) in water, corresponding to increased public concerns regarding their potential negative impacts on urban water systems, and consequently on human life quality. Recently, Advanced Oxidation Processes (AOPs) have been proposed as promising treatment alternatives for effective degradation of NPs in water. However, the selection of appropriate analytical methods for monitoring these oxidation tests remains a challenge. Herein, the feasibility of different characterization strategies for monitoring the evolution of NPs in water upon oxidation tests was systematically studied using polystyrene (PS) NPs of different particle sizes (D0 = 140, 252, 460, and 909 nm) as model plastic pollutants. To quantify NPs in water, Total Organic Carbon (TOC), Chemical Oxygen Demand (COD) and turbidity measurements were assessed. Moreover, turbidity was correlated to the particle size and PS NPs concentration by developing a response surface. Among the analytical techniques employed to characterize the solid particles, transmission electronic microscopy (TEM) was used to evaluate morphology and particle size. Alternatively, the viability of Dynamic Light Scattering (DLS), Nanoparticle Tracking Analysis (NTA) and Atomic Force Microscopy (AFM) to determine particle size is discussed. Chemical surface modifications were explored by Fourier-Transform Infrared Spectroscopy (FTIR). As a proof of concept, the degradation of PS NPs in water upon photoFenteon oxidation was investigated at ambient conditions and fully characterized using the mentioned techniques.